Antifungal efficacy of chitosan nanoparticles against phytopathogenic fungi and inhibition of zearalenone production by Fusarium graminearum - Abdel-Aliem, Hanem A.; Gibriel, Ahmed Y.; Rasmy, Nagwa M. H.; Sahab, Ahmed F.; El-Nekeety, Aziza A.; Abdel-Wahhab, Mosaad Attia (Comunicata Scientiae, 2019)
Chitosan (COS) is a natural safe biopolymer that received great attention in agriculture, food, biomedical, pharmaceutical and environmental industries because their biocompatible, biodegradable, non-toxic and non-allergenic natures. The aims of the current study were to synthesize and characterize chitosan nanoparticles (COS-NPs), to evaluate their antifungal activity against phytopathogenic fungi and inhibition of zearalenone (ZEN) production by Fusarium graminearum. The results revealed that the deacetylation degree of COS was 86.9 0.44 %, the average of molar mass was 171.41 ± 0.29 g/mol, molecular weight was 244 ± 7 kDa and the concentration of free amino groups was 0.05 ± 0.019 mol L-1. COS-NPs showed the nanorod form with rough nature and particle size was around 180 nm. COS-NPs showed an excellent antifungal activity against Alternaria tenuis, Aspergillus niger, A. flavus, Baeuvaria bassiana, Fusarium graminearum, Fusarium oxysporum, Penicillium sp. and Sclerotium rolfsii in dose dependent manner. At a concentration of 800 ppm, it inhibits ZEN production by Fusarium graminearum. It could be concluded that COS-NPs are promise candidate as safe antifungal capable for the prevention of ZEN production.